Thromboelastography Predictive of Death in Trauma Patients - Kane, Ian (Orthop Surg, 2015)
OBJECTIVES: To determine if thromboelastography (TEG) is predictive of patient outcomes following traumatic injury. METHODS: A retrospective review of 131 patients with pelvic trauma admitted to a Level II trauma center was conducted over four years from 1 January 2009 to 31 December 2012. Patients were identified retrospectively from a prospectively collected database of acute pelvic trauma (n = 372). Eligible patients were identified from billing/coding data as having fractures of the acetabulum, iliac wing or sacral alae. Patients with incomplete TEG data were excluded (n = 241), as were patients with pathological fractures. TEG clotting variables and traditional clotting variables were recorded. RESULTS: Evaluation of TEG data revealed 41 patients with abnormal clotting times (TEG R). TEG R > 6 was an independent risk factor for death (OR, 16; 95%CI 5.4–53; P = 0.0001). The death rate was 52% in patients with TEG R values ≥6 (n = 13/25). There was no significant association between traditional clotting markers and death rate. CONCLUSIONS: TEG reaction time value, representing the time of initial clot formation, was the only hematologic marker predictive of mortality in patients with pelvic trauma. Delay in reaction time was associated with a significantly increased death rate, independent of injury severity. The death rate association was not observed with traditional markers of clotting. Future prospective studies may be warranted to determine the presentation and significance of TEG abnormalities when resuscitating patients with orthopaedic trauma.